Potret Pasar Ternak Sumatera Barat - F. Madarisa; Edwardi Edwardi; Armadiyan Armadiyan; Lazuardi Lazuardi (Universitas Andalas, 2012)
A survey to understand the profile of livestock market in West Sumatra had been conducted within three months since August to November 2012. The survey had two objectives; (a) to recognize the stakeholders of livestock markets; and (b) to classify the level of livestock market development. Eighteen livestock markets (69.2 %) have responded to fill a distributed questioner from nine districts and municipalities. Collected data were analyzed by using a simple statistical tools as well as descriptive and qualitative approach. The results showed that there were five components of stakeholders with a different role; (1) farmer, (2) farmers group, (3) middlemen, (4) traders and (5) market officers. Livestock markets could be divided into three categories; (a) big market, (b) middle market and (c) small livestock market. Each category has its own indicators. There was a need to improve the livestock market management to anticipate the external and globalization forces. Then it should be a more transparent transaction process in the internal affairs where market process and products are good, standard, healthy and halal. Therefore livestock markets require an improvement of both at their infrastructures and institutional capacity buildings.